CENTRALHIVE CAPSULE HOSTEL AT BATAM CITY - Tan, Sherly; Wowor, Wulanmeiaya (UJoST- Universal Journal of Science and Technology, 2024)
The business feasibility study of CentralHive Capsule Hostel business in Batam City discusses the concept of capsule hostel with affordable prices for domestic and foreign tourists visiting Batam City. The business feasibility study conducted covers aspects of marketing, operations, human resources, and finance. The location is selected based on the analysis of physical attributes, as well as community support for the capsule hostel concept attached to pre-questionnaire data. Then, in terms of marketing aspects, it includes target market strategy, pricing, and marketing mix. The operational plan involves guest activities, employees, and facilities, while the human resources aspect includes organizational structure and training programs. Financially, this business feasibility study considers initial investment, operational costs, revenue, and financial statement projections. The objective of this business feasibility study is to conduct an in-depth analysis of the capsule hostel accommodation business to be developed, to determine whether the business is feasible or not. The method used is primary data obtained from questionnaires, observations, and structured interviews. There are at least 110 respondents used as samples in this business feasibility study. Based on the conducted analysis, CentralHive Capsule Hostel shows great potential in the hospitality industry